Evaluation formative initiale de la competence interculturelle des apprenants de fle dans le contexte universitaire - Orchowska, Izabela (Glottodidactica, 2005)
The problem discussed in the article refers to a wider context of the empirical research realized within the doctoral dissertation. The research aims at proving the influence of the educational evaluation of the intercultural competence on the development of personal communicative competence of the first year students of French in the College of Foreign Language at the University of Adam Mickiewicz. The evaluation of the competence was conducted in the institutional conditions with the use of traditional media materials in French and Polish. The article introduces the concept of the educational evaluation of intercultural competence. The author also presents the results of the empirical research from its initial phase. The main focus is on the issue of students' metacognitive readiness to perform this type of evaluation. The article aims to show that the positive role of the educational evaluation of intercultural competence in developing personal communicative competence of learners depends to a large extent on the level of metacognitive awareness they managed to reach.